2006
DOI: 10.1086/498558
|View full text |Cite
|
Sign up to set email alerts
|

A Study of the Correlation between the Amplification of the Fe Kα Line and the X‐Ray Continuum of Quasars due to Microlensing

Abstract: The observed enhancement of the Fe Kα line in three gravitationally lensed QSOs (MG J0414+0534, QSO 2237+0305, H1413+117) is interpreted in terms of microlensing, even when equivalent X-ray continuum amplification is not observed. In order to interpret these observations, first we studied the effects of microlensing on quasars spectra, produced by straight fold caustic crossing over standard relativistic accretion disk. The disk emission was analyzed using the ray tracing method, considering Schwarzschild and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
59
0
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 54 publications
(64 citation statements)
references
References 43 publications
3
59
0
2
Order By: Relevance
“…• (see [8] and references therein). The inner radius R in of the disk can not be smaller than the radius of the marginally stable orbit R ms , that corresponds to R ms = 6R g (gravitational radius R g = GM/c 2 , where G is gravitational constant, M is the mass of central BH, and c is the velocity of light) in the Schwarzschild metric and to R ms = 1.23R g in the case of the Kerr metric with angular momentum parameter a = 0.998.…”
Section: Resultsmentioning
confidence: 99%
“…• (see [8] and references therein). The inner radius R in of the disk can not be smaller than the radius of the marginally stable orbit R ms , that corresponds to R ms = 6R g (gravitational radius R g = GM/c 2 , where G is gravitational constant, M is the mass of central BH, and c is the velocity of light) in the Schwarzschild metric and to R ms = 1.23R g in the case of the Kerr metric with angular momentum parameter a = 0.998.…”
Section: Resultsmentioning
confidence: 99%
“…Microlensing variations in H1413+117 may shed light on the nature and structure of the source quasar (e.g., Lewis & Belle 1998;Popović et al 2006). The three time-delay measurements in Section 3 and the new data on the lens (mass and redshift) in Section 4 are useful tools for analyses of microlensing variability.…”
Section: Discussionmentioning
confidence: 99%
“…In several previous papers (Popović et al, 2001(Popović et al, , 2003Popović et al, 2006a;Popović et al, 2006b;Jovanović and Popović, 2007;Jovanović et al, 2008;Jovanović and Popović, 2009) we have shown that the effect of strong gravitational lensing can have influence on the intensity and shape of Fe Kα line. Consequently, this effect can be used as a probe for the structure of the innermost part of lensed quasars.…”
Section: Introductionmentioning
confidence: 55%
“…To select the outer radius R out of the disk, we take into account some recent investigations of the Fe Kα line profile showing that it should be emitted from the innermost part of the disk which outer radius is within several tens of R g (see e.g. Popović et al, 2006a, and references therein). Therefore, in our numerical simulations we adopted the following disk parameters: inclination i = 35 o , inner and outer radii R in = R ms and R out = 20 R g , emissivity index q = −2.5 and angular momentum of central BH a = 0 (Schwarzschild metric).…”
Section: Combined Influence Of Intrinsic Absorption and Gravitationalmentioning
confidence: 99%